An ecological framework including perceived health status for prediction of physical activity in Greek adults - Eleni Theodoropoulou; Konstantinos Karteroliotis (Asociación Española de Ciencias del Deporte, 2015)
Introduction: This cross-sectional study examined an ecological framework including personal, health, psychosocial, and environmental determinants for prediction of physical activity (PA) in Greek adults. Material and Methods: The sample consisted of 684 physically active participants from the Municipality of Athens, 206 men and 478 women (39.16±13.52 years). PA was assessed with the International Physical Activity Questionnaire, which is composed of the walking PA, moderate PA, vigorous PA, and total PA indices. Physical (PCS) and psychological (MCS) health were evaluated using the SF-36 Health Survey, while personal, psychosocial, and environmental predictors were assessed by other valid questionnaires. Separate hierarchical regression analyses were conducted. Results: Findings showed that age, number of children, MCS, exercise self-efficacy, friend support for exercise, and family participation in exercise predicted walking PA, whereas moderate PA was associated with gender, family income, MCS, exercise self-efficacy, and neighbourhood environment. Finally, age, gender, PCS, MCS, exercise self-efficacy, attractiveness, and friend support for exercise predicted vigorous PA, while total PA was associated with gender, PCS, MCS, exercise self-efficacy, attractiveness, and friend support for exercise. Conclusions: These results demonstrated various personal, health, psychosocial, and environmental predictors of PA, indicating that an ecological framework could be useful in the design of PA interventions.